ANALYSIS OF FIRE POST PLACEMENT BASED ON FIRE RISK IN KATINGAN HILIR DISTRICT, KATINGAN REGENCY - Yoshua Paskaputra; Theresia Susi; Singgih Hartanto; Tari Budayanti Usop; Herwin Sutrisno; Petrisly Perkasa (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze fire vulnerability levels and determine the optimal placement of fire stations in Katingan Hilir District, Katingan Regency, Central Kalimantan. Using a quantitative method and spatial modeling approach, the research integrates ten years of NASA MODIS satellite data (2015–2024) focusing on three key variables: fire hotspots, rainfall, and land cover. Findings reveal that 48.5% of the 301 recorded fire hotspots were not covered by the three existing fire stations, with the highest concentration found in Hampangen Village. Based on spatial overlay modeling and a 15-minute response time standard, the study recommends establishing a new fire station in this high-risk area. This spatial assessment offers valuable input for adaptive spatial planning and aims to enhance the regional fire risk management system.